A meta-analysis of factors influencing the strength of mate-choice copying in animals. (9th July 2020) - Davies, Alice D; Lewis, Zenobia; Dougherty, Liam R
Abstract: Mate-choice copying is a form of social learning in which an individual's choice of mate is influenced by the apparent choices of other individuals of the same sex and has been observed in more than 20 species across a broad taxonomic range. Though fitness benefits of copying have proven difficult to measure, theory suggests that copying should not be beneficial for all species or contexts. However, the factors influencing the evolution and expression of copying have proven difficult to resolve. We systematically searched the literature for studies of mate-choice copying in nonhuman animals and, then, performed a phylogenetically controlled meta-analysis to explore which factors influence the expression of copying across species. Across 58 published studies in 23 species, we find strong evidence that animals copy the mate choice of others. The strength of copying was significantly influenced by taxonomic group; however, sample size limitations mean it is difficult to draw firm conclusions regarding copying in mammals and arthropods. The strength of copying was also influenced by experimental design: copying was stronger when choosers were tested before and after witnessing a conspecific's mate choice compared to when choosers with social information were compared to choosers without. Importantly, we did not detect any difference in the strength of copying between males and females or in relation to the rate of multiple mating. Our search also highlights that more empirical work is needed to investigate copying in a broader range of species, especially those with differing mating systems and levels of reproductive investment. Abstract : Meta-analysis shows that both male and female animals are more likely to copy, rather than avoid, the mate choices of their rivals. We analyzed the results of 58 studies testing how animal mate choice is influenced by seeing the choice of a rival. We found that animals do copy the choices of rivals, though copying was strongest in mammals and weakest in invertebrates. Both males and females copied to a similar degree.